Key performance indicators in some selected Malaysian small medium hotel industry - Mohamed, Rapiah; Muhammad Jamil, Che Zuriana (2014)
In recent years, performance measurement systems (PMS) have received much attention from researchers and practitioners.However, prior literature more focus on the PMS in large corporation, and, very little research done in small medium enterprises (SME).This paper reports the results of an empirical study on the key performance indicators employed in small medium hotel enterprises.The data were collected using a mail survey to the hotel managers. The finding indicates that small hotels adopt multi-dimensional of performance indicators that combined both financial and non-financial measures. The result also shows that multi-dimensional performance indicators has a positive correlation with hotel’s performance.